2021
DOI: 10.3390/antiox10101620
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid C Protects against Cisplatin-Induced Acute Kidney Injury through Attenuation of Inflammation, Oxidative Stress and Apoptotic Effects and Activation of the CaMKK–AMPK–Sirt1-Associated Signaling Pathway in Mouse Models

Abstract: Acute kidney injury (AKI) is a sudden reduction in kidney activity and has a high mortality rate. Salvianolic acid C (SAC), one of the main polyphenolic components of Salvia miltiorrhiza, displays significant pharmacologically active effects. An animal model of cisplatin-induced kidney injury was used to study the potential of SAC to improve AKI. First, SAC was administered intraperitoneally in mice for 10 consecutive days, and then cisplatin was administered intraperitoneally on day 7 to establish a nephrotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 61 publications
(78 reference statements)
1
21
0
Order By: Relevance
“…In this study, the Cp-injected rats demonstrated deliberate oxidative stress in the kidneys indicated by a significant increase in lipid peroxidation along with the depletion of total antioxidants levels and reduced catalase activity. These findings were consistent with those reported by previous studies [ 27 , 51 , 52 , 53 ]. ROS can activate both inflammatory and apoptotic pathways.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, the Cp-injected rats demonstrated deliberate oxidative stress in the kidneys indicated by a significant increase in lipid peroxidation along with the depletion of total antioxidants levels and reduced catalase activity. These findings were consistent with those reported by previous studies [ 27 , 51 , 52 , 53 ]. ROS can activate both inflammatory and apoptotic pathways.…”
Section: Discussionsupporting
confidence: 94%
“…In the current work, cisplatin caused downregulation of ovarian AMPK mRNA expression compared to the control group. Cisplatin has been reported to cause renal injury through the downregulation of AMPK expression [86,87]. In contrast, melatonin co-administration with cisplatin increased the expression of AMPK mRNA in the ovarian tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of TLR4 on renal parenchymal cells may activate the p38 MAPK pathway, leading to increased production of inflammatory cytokines such as TNF-α and subsequent renal injury ( 39 ). Salvianolic acid C ( 40 ), Cordyceps cicadae Mycelia ( 41 ) reduce the expression level of TLR-4 and enhance several antioxidant enzymes (superoxide dismutase and glutathione peroxidase) to alleviate cisplatin induced AKI. Consistent with the above results, our results showed that TLR4 mRNA levels were significantly elevated in cells and mouse models of DI-AKI.…”
Section: Discussionmentioning
confidence: 99%